2018
DOI: 10.1007/s11845-018-1820-3
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of lipid levels in the Republic of Ireland in 2017

Abstract: This pilot study reveals significant lipid abnormalities which require further larger more detailed lipid studies to assess the true burden of lipid abnormalities in Ireland. Cascade screening and genetic testing of relatives of those with severe lipid abnormalities should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Multiple subjects had TG values less than 45 mgÁdL À1 on at least 1 day, resulting in the inability to calculate LDL-C. Additionally, one subject exceeded 100 mgÁdL À1 for HDL-C on days 1 and 11. While this lipid cassette may be less valid compared with the gold standard CLIA-certified human diagnostic laboratory, 19 it has been used previously in field research, [20][21][22] with a coefficient of variation of less than 5% and intraclass correlation coefficients more than 0.8. 23 To measure hemoglobin A1c (HbA1c) on days 1 and 11, 1 mL of whole blood was transferred into a DCA HbA1c reagent kit and loaded into a DCA Vantage Analyzer (Siemens Healthineers, Malvern, PA).…”
Section: Blood Analysismentioning
confidence: 99%
“…Multiple subjects had TG values less than 45 mgÁdL À1 on at least 1 day, resulting in the inability to calculate LDL-C. Additionally, one subject exceeded 100 mgÁdL À1 for HDL-C on days 1 and 11. While this lipid cassette may be less valid compared with the gold standard CLIA-certified human diagnostic laboratory, 19 it has been used previously in field research, [20][21][22] with a coefficient of variation of less than 5% and intraclass correlation coefficients more than 0.8. 23 To measure hemoglobin A1c (HbA1c) on days 1 and 11, 1 mL of whole blood was transferred into a DCA HbA1c reagent kit and loaded into a DCA Vantage Analyzer (Siemens Healthineers, Malvern, PA).…”
Section: Blood Analysismentioning
confidence: 99%
“…Studies suggest a decline in cholesterol levels in Ireland since the 1980s [49][50][51]. A recent study identified one possible FH case among 259 of the public screened [49].…”
Section: Irelandmentioning
confidence: 99%
“…Studies suggest a decline in cholesterol levels in Ireland since the 1980s [49][50][51]. A recent study identified one possible FH case among 259 of the public screened [49]. A national FH database has been initiated, supported by industry, which also funds lipid nurses for FH screening.…”
Section: Irelandmentioning
confidence: 99%
“…The extent of lipid problems in Ireland is significant, and lipid management [4,6] and lipid services are inadequate [15,16]. The significance of untreated lipid disorders on population health cannot be overestimated [17,18], and early interventions could have far-reaching consequences on Irish lives and health care resource utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…2) was also produced to help guide interpretation when needed. A number of hyperlink materials were also developed to help familiarise practitioners with information that would enhance their understanding of the basis for intervention and need for further screening as deemed necessary [10][11][12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%